Palynology and Vegetation History - Valent (Frontiers Research Topics, 2019)
This Research Topic commemorates the centenary of the first quantitative pollen diagram by Lennart von Post, the founder of paleoecological palynology. The main aim is to provide a thorough view of the use of palynology in aspects such as the reconstruction of Quaternary vegetation and environmental changes, the role of natural and anthropogenic drivers in the development of the Quaternary vegetation, the shaping of present-day ecological and biogeographical patterns, the potential application of this knowledge in biodiversity conservation and landscape restoration and the development of new methods of pollen analysis and data management. The Research Topic is subdivided into four main conceptual parts, namely (1) modern analog studies; (2) land cover estimates from pollen data; (3) vegetation dynamics reconstructions from Europe, North and South America, Africa and Oceania; and (4) large-scale reviews and meta-analyses. Hopefully, this Research Topic will serve to appraise the state of the art of modern palynology and highlight the usefulness of this discipline in long-term ecological research.